2015
DOI: 10.1021/acs.organomet.5b00608
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fluorine Substituents in the Regioselectivity of Intramolecular C–H Bond Functionalization of Benzylamines at Palladium(II)

Abstract: The effect of fluorine substituents on the regio­selectivity of intramolecular reactions of mono- and difluorinated N,N-dimethylbenzylamines (1a–f) at palladium, to form palladacycles di-μ-acetato­bis­[o-dimethylaminomethyl-n-fluorophenyl-C,N)­dipalladium­(II) (2a–f) and di-μ-chloro­bis­[o-dimethylaminomethyl-n-fluorophenyl-C,N)­dipalladium­(II) (3a–e), has been investigated. When fluorinated substrates with two sites available for the C–H functionalization (1c and 1e) undergo cyclopalladation via a CMD mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…At the same temperature and concentration used in catalysis, complex 7accounts for approximately half of the total palladium loading as assessed by 1 H NMR spectroscopy (SI Figure 10 -11). The stoichiometry of the bridge splitting complex was confirmed with MCV and is consistent with the bridge splitting equilibria observed with isolated dimers 64,65 and in systems with bimetallic 36,66 active catalysts (SI Figure 13).…”
Section: Resultssupporting
confidence: 82%
“…At the same temperature and concentration used in catalysis, complex 7accounts for approximately half of the total palladium loading as assessed by 1 H NMR spectroscopy (SI Figure 10 -11). The stoichiometry of the bridge splitting complex was confirmed with MCV and is consistent with the bridge splitting equilibria observed with isolated dimers 64,65 and in systems with bimetallic 36,66 active catalysts (SI Figure 13).…”
Section: Resultssupporting
confidence: 82%
“…With meta-substituted ligands L2-R most reactions proceed with para selectivity, and it is only with L2-F that the ortho isomer is favored both kinetically and thermodynamically. The formation of a mixture of ortho- and para-cyclometalated products in the reactions of fluorinated dimethylbenzylamines at [Pd­(OAc) 2 ] has previously been taken as evidence for an AMLA mechanism rather than S E Ar . The para-selectivity is predominantly steric in origin; however, the observation of ortho-H/D exchange with some L2-R ligands reveals an unexpectedly accessible C–H activation ortho to the substituent R. Indeed, ortho-C–H activation can even be faster than para-C–H activation, as seen in the greater amount of ortho-deuteration observed for L2-NMe 2 at Ir and L2-OMe at Rh.…”
Section: Discussionmentioning
confidence: 99%
“…33 In contrast, Fairlamb et al have recently shown that the regioselectivity of the cyclometalations of fluorinated dimethylbenzylamines at Pd is dependent on the Pd precursor used. 34 Thus, with [Pd(OAc) 2 ] roughly equal amounts of the ortho and para products are formed, whereas Li 2 PdCl 4 gave exclusively the para isomer. Both reactions were proposed to be under kinetic control, with the former suggested to proceed via an AMLA/ CMD mechanism and the latter more likely via S E Ar.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Can C-H activation involving polynuclear complexes lead to different regioselectivities in comparison with the mononuclear pathway? 19 How are reactivity and nuclearity influenced by the addition of carboxylates of different metals? 20 What is the role of polynuclear complexes in the ongoing catalytic cycles of C-H functionalization reactions, where their formation is less probable?…”
Section: Discussionmentioning
confidence: 99%